The Place of the Spirit Toward a Trinitarian Theology of Location. - Morice-Brubaker, Sarah (Havertown : James Clarke & Co, 2014)
The Place of the Spirit'' is through and through a constructive work. It brings together a representative sample of thinkers of place, none of whom are theological in the strict sense, and asks the question whether, and if so how, this thinking can be brought productively to bear on Trinitarian thought and correspondingly whether, and if so in what way, Trinitarian thought can shed unexpected light on placial theories. Towards this end, Sarah Morice-Brubaker inserts the placial theories of Martin Heidegger and Edward Casey, Gaston Bachelard and Yi-Fu Tuan in two interlocking conversations. The.
Front Cover; Title Page; Copyright information; Contents; Foreword; Acknowledgments; 1. Placing the Question; 2. Patristic Precedents; 3. Moltmann's Perichoretic Spaces for God and Creation; 4. No Place for the Spirit? Jean-Luc Marion's Placial Refusal; 5. Notes Toward a Trinitarian Theology of Place; Bibliography; Back Cover.
Print version record.
Master record variable field(s) change: 072
Keywords: Sacred space; Place (Philosophy); Place (Philosophy); Sacred space; RELIGION -- Christian Theology -- General; Place (Philosophy); Sacred space; RELIGION / Christian Theology / General; Electronic books